Mieniplotia scabra (Müller, 1774), another gastropod invasive species in Europe and the status of freshwater allochthonous molluscs in Greece and Europe - CIANFANELLI, S.; TALENTI, E.; BODON, M. (Mediterranean Marine Science, 2016)
Mieniplotia scabra (Müller, 1774), a freshwater gastropod originating from the Indo-Pacific area, has proved to be a successful invader spreading to other parts of East Asia, Middle East, the Pacific Islands, North America and West Indies. This paper reports the first record of M. scabra from Europe, where it has become naturalized in Kos Island in Greece. This new trans-continental introduction brings to nine the number of alien freshwater molluscs species in Greece and to 30 in Europe. It is therefore given an updated snapshot on the presence of the numerous non-native fresh water species in Europe, divided by nation, an account that is currently lacking in literature and in the specific databases.